The president and the viper : political satire and conceptual blending theory - Berberović, Sanja (Array, 2020)
Applying conceptual blending theory, the paper analyses the construction of the meaning of a satirical text ridiculing the language employed by politicians to frame the debate on current political and social issues. In particular, it focuses on the language used by Donald Trump in explaining his anti-immigration stances through a poem based on the fable about the farmer and the viper, and a satirical text providing a new version of the poem, which criticizes Trump’s immigration policy. The paper examines the creation of the humorous meaning of the text in conceptual blending. The humorous meaning is created in the blended space due to the unusual combination of related structures, which results in incongruity (Coulson 2002; Marín-Arrese 2003). Furthermore, as blending can be used as a rhetorical tool influencing the audience to change the reality and even act upon it (Coulson 2006; Coulson & Oakley 2006; Coulson & Pascual 2006; Oakley & Coulson 2008), the analysis of the construction of the meaning of the satirical text as a product of conceptual blending can reveal rhetorical and argumentative goals in political discourse.